Research on Unified Energy Efficiency Evaluation Method for Heat Pump and Electric Water Heater Based on Dynamic Water Usage Mode☆ - XIA Yujuan; CHEN Haihong; QI Xin; LIN Haoxin; WU Xiaoli; SHI Liming (Zhileng xuebao)
In response to the problem of inconsistent energy efficiency evaluation indicators between air source heat pumps and storage type electric water heaters in China, this study proposes a unified energy efficiency evaluation method based on 24-hour dynamic water use tests. By analyzing the hot water usage habits of Chinese residents, a typical water usage pattern was established that includes water usage time distribution, temperature demand, and flow characteristics. A unified evaluation index based on primary energy utilization efficiency was also designed. Experimental verification shows that the primary energy efficiency of heat pump water heaters (67.7%~99.2%) is significantly higher than that of storage electric water heaters (31.5%~36.4%).